Impacts of REDD+ in Mexico: Experiences of Two Local Communities in Campeche - Jovanka Špirić (El Colegio de la Frontera Sur, 2021)
In 2010, the Mexican National Forestry Commission (Spanish acronym CONAFOR) implemented REDD+ early action activities in priority states, including Campeche. This article explores the impact of the forestry programs promoted under REDD+ on the diversification of household activities, benefit-sharing among local groups, and forest cover changes in two local communities in Campeche. It examines whether the design and implementation of these programs responded to local aspirations for equity and rural development by combining ethnographic and documental methods. In addition, it quantifies land-cover change (2013-2018) using high-resolution imagery and spatial analysis. It found no intracommunity equity or sustainable activity diversification resulting from the REDD+ implementation. Deforestation for livestock and agricultural mechanization was the dominant process observed both in dense and open forests. Although it has not made the situation worse, REDD+ has yet to provide social benefits for these two communities. To be considered a viable option locally, the program design under REDD+ must combine the implementation of several sustainable productive activities over a longer period and provide net monetary benefits to all local groups.